2000
DOI: 10.1038/35012518
|View full text |Cite|
|
Sign up to set email alerts
|

The DNA sequence of human chromosome 21

Abstract: Chromosome 21 is the smallest human autosome. An extra copy of chromosome 21 causes Down syndrome, the most frequent genetic cause of significant mental retardation, which affects up to 1 in 700 live births. Several anonymous loci for monogenic disorders and predispositions for common complex disorders have also been mapped to this chromosome, and loss of heterozygosity has been observed in regions associated with solid tumours. Here we report the sequence and gene catalogue of the long arm of chromosome 21. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
533
4
11

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,083 publications
(568 citation statements)
references
References 41 publications
9
533
4
11
Order By: Relevance
“…the sequences of Neisseria meningitidis [57], D. radiodurans [58], Drosophila melanogaster [59], chromosomes 2 and 4 from Arabidopsis thaliana [60,61], chromosomes 2 and 3 from Plasmodium falciparum [62,63], and chromosomes 21 and 22 from Homo sapiens [64,65] that were recently reported. For the few cases of homologies to these organisms, refer to [37^49].…”
Section: F Tekaia Et Al/febs Letters 487 (2000) 17^30mentioning
confidence: 92%
“…the sequences of Neisseria meningitidis [57], D. radiodurans [58], Drosophila melanogaster [59], chromosomes 2 and 4 from Arabidopsis thaliana [60,61], chromosomes 2 and 3 from Plasmodium falciparum [62,63], and chromosomes 21 and 22 from Homo sapiens [64,65] that were recently reported. For the few cases of homologies to these organisms, refer to [37^49].…”
Section: F Tekaia Et Al/febs Letters 487 (2000) 17^30mentioning
confidence: 92%
“…For probes, BAC (bacterial artificial chromosome) clones derived from chromosome 21 were selected from the published chromosome 21 contig 17 and personal communications from Dr Yaspo. BAC clone RP11-2503J9 was obtained from the Max-Planck-Institut fur Molekulare Genetik.…”
Section: Fish (Fluorescence In Situ Hybridization) Analysismentioning
confidence: 99%
“…DCR-2 has been associated with certain facial and dermatoglyphic features, mental retardation, congenital heart disease, as well as duodenal stenosis (Korenberg et al, 1994). Human WDR9 was identified as a transcribed sequence within DCR-2 (Vidal-Taboada et al, 1998;Hattori et al, 2000). The expression of this transcript was further examined recently, and results indicated that human WDR9 is widely expressed in different human adult tissues and several cell lines with tissue-specific transcripts (Ramos et al, 2002).…”
Section: Introductionmentioning
confidence: 99%